Influências metodológicas na mensuração de impacto: o caso das Memórias do Instituto Oswaldo Cruz e sua “qualificação” (Perspectivas em Ciência da Informação, 2009)
In recent years, the offer of citation indexes for evaluation of Brazilian scientific production has increased. The comparison among the results of the methodologies used to estimate indicators, in the citation reports of SciELO database and in Journal Citation Reports (ISI-Thomson Scientific) made possible to evaluate implications associated to scientific the Brazilian scientific policy (Qualis), regarding some of specific criteria. It was considered a period of 10 years, taking account two bibliometric indicators (the total of citations in a year and the Impact Factor) of the journal Memórias do Instituto Oswaldo Cruz, which is indexed in both indexes. The correction of the indicators associated to this journal showed that the differences available by the citation indexes were more expressive in 2001, having decreased in the last years. This reduction gives credibility to both databases, validating their systems for the production of bibliometric indicators.